2001
DOI: 10.5194/angeo-19-1119-2001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength imaging observations of plasma depletions over Kavalur, India

Abstract: Abstract.Observations of ionospheric plasma depletions were made over Kavalur (12.56 • N, 78.8• E, Mag. Lat 4.6• N), India during March-April 1998 using an all sky optical imaging system operating at 630 nm, 777.4 nm and 557.7 nm. Out of 14 nights of observations, plasma depletions were seen only on 9 nights. Except for 21 March 1998, which was a magnetically disturbed period, all other nights belonged to a magnetically quiet period. Some of the important results obtained from these observations are: (a) Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…They suggested that the disturbance electric fields and currents act to reduce or reverse the normal S q current system over low equatorial latitudes. The recent observations of plasma depletions by Sinha et al (2001) using multiwavelength imaging system from Kavalur (India), a low latitude station, on a magnetically disturbed night are equally relevant. The drift speed of these depletions was found to be far lower than on normal nights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the disturbance electric fields and currents act to reduce or reverse the normal S q current system over low equatorial latitudes. The recent observations of plasma depletions by Sinha et al (2001) using multiwavelength imaging system from Kavalur (India), a low latitude station, on a magnetically disturbed night are equally relevant. The drift speed of these depletions was found to be far lower than on normal nights.…”
Section: Discussionmentioning
confidence: 99%
“…The drift speed of these depletions was found to be far lower than on normal nights. Sinha et al (2001) attributed the sluggish drift speed of plasma depletions to severe modification of the F-region dynamo electric fields affected by direct penetration of disturbance electric fields from high latitudes to low latitudes. However, their observations concern a magnetically disturbed period which would normally follow a day or two after the occurrence of a solar flare.…”
Section: Discussionmentioning
confidence: 99%
“…The cosmic noise absorption measurement (at 30 MHz) has been done from Kolhapur to study the effect of solar noise and local noise on ionosphere (Nikte et al, 2014). Several investigators have been using ASI (OI 630.0 nm emission) to study the onset, evolution and dynamics of EPBs (e.g., Weber et al, 1980;Sahai et al, 1994;Taylor, 1997;Mukherjee and Shetti, 2008;Fagundes et al, 1999;Sinha et al, 2007;. It is of scientific interest to study the characteristics and morphology of EPBs because they cause random error and scintillations in the satellite signals which results in barrier in communication and navigation system.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements have significantly improved our understanding of the gravity‐wave characteristics. At the same time, several studies of 630.0 nm O ( 1 D) thermospheric airglow emission and total electron content (TEC) measurements have strengthened our knowledge of thermosphere‐ionosphere system behavior [e.g., Mukherjee et al , 2000; Sinha et al , 2001; Ogawa et al , 2002; Makela and Miller , 2008].…”
Section: Introductionmentioning
confidence: 99%